My Home is My Castle - Kleider, Alexander; Michel, Daniela; Müller, Marco (Dok-Werk Filmkooperative, 2011)
Verzio FF Duration: 01:15:00 Different aspects of the struggle to secure a future in ever-changing Hungarian society: some struggle to preserve the roof over their heads, some struggle with the pressure to perform, while others face constantly growing racism. Szabina, a young Roma violinist, is struggling for her future as a musician. Balint, a highly gifted child from a rich family, does not need to worry about financial matters, but he suffers from the high expectations everyone has of him. Kazmer and Ica, like countless other homeless people, try their luck in the woods: they built a shack from waste wood and hope to find a "normal" apartment in the city one day. But when the city council orders the clearing of the forest huts, they are facing the loss of their dignity. The film follows their lives for a year and through their stories it shows that hope, humanity and the joy can be found even under the most difficult circumstances.